2020
DOI: 10.1002/gea.21787
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Midden: Geoarchaeological investigation of sedimentation processes, waste disposal practices, and resource management at the La Tène settlement of Basel‐Gasfabrik (Switzerland)

Abstract: To interpret artifact assemblages, it is necessary to understand the processes that have formed and influenced them: layer formation processes, cultural practices, and the way resources were used. In this study, we present our results of micromorphologically analyzed pits, ditches, house floors, and occupation layers found within the younger Iron Age settlement of Basel‐Gasfabrik. We defined 11 microfacies types and put them into a spatial and stratigraphic context. In addition, we quantify waste categories ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Nevertheless, reconstructing house plans proved very difficult, although micromorphological investigations did identify rammed earth floors. The analyses revealed that no (micro-) remains (de facto refuse) could be detected directly above these house floors [30]. It is therefore assumed that the floors were kept clean or covered.…”
Section: Plos Onementioning
confidence: 94%
See 4 more Smart Citations
“…Nevertheless, reconstructing house plans proved very difficult, although micromorphological investigations did identify rammed earth floors. The analyses revealed that no (micro-) remains (de facto refuse) could be detected directly above these house floors [30]. It is therefore assumed that the floors were kept clean or covered.…”
Section: Plos Onementioning
confidence: 94%
“…The infilling processes were reconstructed by geoarchaeological means and initial taphonomic investigations of ceramic sherds and animal bones were carried out. This resulted in the hypothesis that objects deposited in pits are generally better preserved than those found elsewhere within the settlement [30].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations